Clinical Study to Determine the Efficacy of Percutaneous Vertebroplasty in Management of Osteoporotic Compression Fracture (Medico Legal Update, 2021)
Introduction: Back pain and spinal deformity are common presentation in majority of senile osteoporoticvertebral compression fracture. Vertebroplasty provides pain relief with correction of spinal deformity andleast period of hospital stay.Material and Method: Twenty patients underwent vertebroplasty and clinical evaluation of pain was doneby recording the VAS score done preoperatively and after surgery.Result: Percutaneous vertebroplasty with 1 year followup.VAS score 52% were excellent,14% good and34% fair result.Conclusion: Vertebroplasty is useful in management of vertebral compression fracture which are refractoryto conservative treatment & helps in early mobilization.